A Firm's First Year - Jaap H. Abbring; Jeffrey R. Campbell (Tinbergen Institute, 2005)
This paper determines the structural shocks that shape a firm's first year by estimating a structural model of firm growth, learning, and survival using monthly sales histories from 305 Texas bars. We find that heterogeneity in firms' pre-entry scale decisions accounts for about 40% of their sales' variance; persistent post-entry shocks account for most of the remainder. We find no evidence of entrepreneurial learning. Variation of the firms' fixed costs consistent with an annual lease cycle explains their exit rates. We use the estimated model to price a new bar's option to exit, which accounts for 124% of its value.
Keywords: C34; D83; L11; L83; 330; firm exit; option value; fixed costs; Bayesian learning; Unternehmenswachstum; Unternehmenserfolg; Lernende Organisation; Theorie; Marktaustritt